Implementasi Peran Guru Penggerak dalam Pembentukan Karakter Siswa Berorientasi Pada Nilai-Nilai Pancasila - Fransiska Kristiani Harefa; Amstrong Harefa; Anugerah Tatema Harefa; Fatiani Lase (Pusat Riset dan Inovasi Nasional, 2025)
The driving teacher is a learning leader who encourages student growth and development holistically, actively, proactively in moving a better educational ecosystem through the collaboration of various parties. The research aims to describe the role, obstacles and efforts to overcome the obstacles of the driving teacher in values-oriented student character building. The descriptive approach qualitative research method aims to provide an accurate description of the phenomena that occur. Data collection techniques: observation, interview, documentation. Informants totaled five people, principals, driving teachers, students. Data analysis techniques are collecting, analyzing data and drawing conclusions. The results of the study: the role of the driving teacher is to teach, guide, train, familiarize the character by doing things that must be followed by students and practicing the values of Pancasila; the obstacles of the driving teacher are that some students still do not follow the guidance and direction of the driving teacher and limited infrastructure; efforts to overcome the obstacles of the driving teacher, namely the driving teacher is able to develop creative, interactive and relevant learning methods with students' lives.